Generic acoustics prediction model engine - Fischer, Travis J. (My University, 2010)
Trane Company in La Crosse, WI has a continual need for software systems that can calculate predictions of the acoustic performance for their air conditioning products. A suite of acoustic prediction software tools has been developed and maintained at Trane over the last 20 years. Over time these legacy software tools have become cumbersome and expensive to maintain. This manuscript describes the development of a software system designed to make these acoustics prediction calculations for various Trane air conditioning products. The software system includes a software library with a public API that will be used by various Trane software systems in order to make acoustic calculations. The system also includes a graphical user interface application that will be deployed to Trane engineers and sales people in order to allow them to more easily make acoustic calculations.
Keywords: Application software -- Development; Air conditioning -- Equipment and supplies -- Noise; Trane Company